Developing STEM Learning Design with Mini Projector Media in Grade V of Elementary School - Opi Irmayani; Dindin Abdul Muiz Lidinillah; Agnestasia Ramadhani Putri (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2023)
The lack of innovation in process engineering and technology-based learning in primary schools results in suboptimal learning outcomes. Primary school education does not involve students directly in every learning process, leading to underdeveloped student competencies. One innovative learning approach that can be utilized by elementary school teachers is STEM (Science, Technology, Engineering, and Mathematics) education. The objective of this research is to develop a STEM learning design product to make primary school education more meaningful. The research method employed is Educational Design Research (EDR), which consists of three phases: analysis and exploration, design and construction, and evaluation and reflection. Data collection techniques include interviews, observations, documentary studies, and questionnaires. The subjects of this research are students from classes VB and VC at SDN 2 Pengadilan Kota Tasikmalaya. After conducting two trials of the STEM learning design, it was found that the developed learning design is valid, practical, and suitable for use in primary schools. STEM education can serve as an alternative for teachers to implement learning processes that involve engineering and technology, thus meeting the demands of 21st-century skills for students.